The safety pharmacology of Syk inhibitors: new preclinical screens to characterise cardiovascular adverse drug effects - Van Daele, Marieke (2024)
Since the implementation of ICH S7A, the field of safety pharmacology has advanced radically. Current approaches for detection of cardiovascular (CV) adverse drug reactions (ADR), including evaluating mean arterial pressure (MAP) and heart rate (HR) often identify those safety risks. Nonetheless, high attrition rates due to safety issues remain an important challenge in drug development. Conventional analysis (MAP or HR) uses a minority of the recorded high-fidelity waveform data, overlooking a plethora of information. Potentially in-depth analysis of the CV waveform could provide early and mechanistically relevant markers to detect subtle CV ADR and aid in closing the current gaps in safety pharmacology. The Symmetric Projection Attractor Reconstruction (SPAR) is a novel in-depth wave analysis method that uses the entire waveform to generate an attractor which reflects and enlarges subtle changes in the wave. In this thesis, the application of SPAR on blood pressure and blood flow waves in CV safety pharmacology was explored. To perform this investigation, two tyrosine kinase inhibitors were selected and presented as an example of compounds with varying CV safety liabilities: (1) fostamatinib that targets Syk but is associated with the onset of hypertension due to off-target inhibition of Vascular Endothelial Growth Factor Receptor 2 (VEGFR2) and (2) entospletinib, a second-generation compound designed to not bind VEGFR2 and to achieve Syk inhibition without the onset of cardiovascular safety liabilities.